X-ray structure based evaluation of analogs of citalopram: Compounds with increased affinity and selectivity compared with R-citalopram for the allosteric site (S2) on hSERT. Issue 3 (1st February 2017) - Topiol, Sid; Bang-Andersen, Benny; Sanchez, Connie; Plenge, Per; Loland, Claus J.; Juhl, Karsten; Larsen, Krestian; Bregnedal, Peter; Bøgesø, Klaus P.
Graphical abstract: Abstract: The recent publication of X-ray structures of SERT includes structures with the potent antidepressant S-Citalopram (S-Cit). Earlier predictions of ligand binding at both a primary (S1) and an allosteric modulator site (S2), were confirmed. We provide herein examples of a series of Citalopram analogs, showing distinct structure-activity relationship (SAR) at both sites that is independent of the SAR at the other site. Analogs with a higher affinity and selectivity than benchmark R-Citalopram (R-Cit) for the S2 versus the S1 site were identified. We deploy structural and computational analyses to explain this SAR and demonstrate the potential utility of the newly emerging X-ray structures within the neurotransmitter:sodium Symporter family for drug design.